Temperature-sensitive Yeast Mutant Defective in Ribonucleic Acid Production - Hutchison, H. Terry (1969)
A single, recessive mutation in a nuclear gene confers a temperature-sensitive growth response in a mutant of Saccharomyces cerevisiae, ts(−) 136. The mutant grows normally at 23 C, but exhibits a rapid and preferential inhibition of ribonucleic acid (RNA) accumulation after a shift to 36 C, demonstrating a defect in stable RNA production. Cultures of the mutant which were shifted from 23 to 36 C display the following phenomena which indicate that messenger RNA (mRNA), as well as stable RNA production, is defective. The entrance of pulse-labeled RNA into cytoplasmic polyribosomes is even more strongly inhibited than is net RNA accumulation. The rate of protein synthesis, at first unaffected, decreases slowly; this decrease is paralleled by the decay of polyribosomes to monoribosomes with a half-time of 23 min. The polyribosomes which remain after a 30-min preincubation of the mutant at 36 C are active in polypeptide synthesis in vivo, whereas the monoribosomes which accumulate are not. Furthermore, ribosomes isolated from a culture of the mutant preincubated for 1 hr at 36 C are inactive in polypeptide synthesis in vitro, but can be restored to full activity by the addition of polyuridylic acid as mRNA. We conclude that mutant ts(−) 136 is defective either in the synthesis of all types of cytoplasmic RNA, or in the transport of newly synthesized RNA from the nucleus to the cytoplasm, and that the mRNA of a eucaryotic organism (yeast) is metabolically unstable, having a half-life of approximately 23 min at 36 C.